Cross Inhibition of MPK10 and WRKY10 Participating in the Growth of Endosperm in Arabidopsis thaliana - Xi, Xiaoyuan; Hu, Zhengdao; Nie, Xuerui; Meng, Mingming; Xu, Hao; Li, Jing (Frontiers in plant science, 2021)
The product of double fertilization produces seed, which contains three components: triploid endosperm, diploid embryo, and maternal seed coat. Amongst them, the endosperm plays a crucial role in coordinating seed growth. Mitogen-activated protein kinase (MAPK) cascades are conserved in eukaryotes and involved in signal transduction of plant development. MPK3, MPK6, and MPK10 form a small group of MPKs family in Arabidopsis thaliana . MPK3 and MPK6 are extensively studied and were found to be involved in diverse processes including plant reproduction. However, less is known about the function of MPK10. Here, we found WRKY10/MINI3 , a member of HAIKU (IKU) pathway engaging in endosperm development, and MPK10 is high-specifically expressed in the early developmental endosperm but with opposite gradients. We further proved that MPK10 and WRKY10 cross-inhibit the expression of each other. The inhibition effect of MPK10 on gene expression of WRKY10 and the downstream targets is supported by the fact that MPK10 interacts with WRKY10 and suppresses the transcriptional activity of WRKY10. Constantly, mpk10 mutants produce big seeds while WRKY10/MINI3 positively regulate seed growth. Altogether, our data provides a model of WRKY10 and MPK10 regulating endosperm development with a unique cross inhibitory mechanism.